2021
DOI: 10.1051/shsconf/20219203004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of global changes in the business environment in relation to risk management

Abstract: Research background: Entrepreneurial activity is largely affected by negative changes in the global business environment, as evidenced by the huge impact of the COVID 19 pandemic on the entrepreneurial activity of Slovak enterprises. It is here that the importance of proactive risk management is reaffirmed, which should be an integral part of the enterprise’s management and thus preventively assess possible risks and their consequences and be prepared to manage them and not just respond to a crisis situation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(2 reference statements)
0
1
0
Order By: Relevance
“…In the context of globalization, due to the intensity and interconnection of risk sources, but also the high number of risk sources, an increasingly complex task for enterprises is their internationalization (Buganová et al, 2021). From the analysis performed, it is observed that, compared to 2014, in 2018, in all countries there are increases in the values of employees for control entities from within the EU, except Belgium.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of globalization, due to the intensity and interconnection of risk sources, but also the high number of risk sources, an increasingly complex task for enterprises is their internationalization (Buganová et al, 2021). From the analysis performed, it is observed that, compared to 2014, in 2018, in all countries there are increases in the values of employees for control entities from within the EU, except Belgium.…”
Section: Discussionmentioning
confidence: 99%
“…Perkembangan di era globalisasi saat ini, masalah sumber daya manusia menjadi tumpuan bagi perusahaan yang utamanya menjaga produktivitas kerja karyawan itu sendiri. Segala tuntutan perusahaan dalam mempertahankan dan mengelola sumber daya manusia yang berkualitas semakin mendesak oleh adanya dinamika lingkungan yang berubah (Buganová et al, 2021;Djaja & Arief, 2015). Dikatakan produktif apabila sumber daya tersebut memiliki produktivitas kerja yang tinggi serta dapat mencapai sasaran atau target yang telah ditentukan dan dapat bertanggung jawab menyelesaikan tugas dengan tepat waktu.…”
Section: Pendahuluanunclassified